Image watching system with remote direct based on mobile communication - Koc, Yahya; Albayrak, Songul (IEEE, 2006)
Nowadays mobile communication has become widespread. Mobile phones are used not only voice communication but also to send different data types (voice, image,text),for entertainment (listening music,playing games), for remote access and remote control. Now, mobile phones have become handy computers. The mobile phone manufacturers which stand in competition with each other have begun to put on the market new models which have new capabilities. Mobile phones software development market has grown up with these developments. The developers who interested in this technology must challenge with many obstacles. One of these obstacles is the documentation shortness. By passage of time this technology will become prevalent and samples codes and documents will increase. In this way development time period will decrease and costs will drop.
Keywords: Computer Science; Engineering; Imaging Science & Photographic Technology